The Influence Interpersonal Conflict and Group Collaboration To Skills Presentation Office Administrative Education Students Class of 2022 - Poluan, Nadia Amelia Elyana; Situmorang, Yulistira; Simangunsong, Diah Permata Nadia (Talenta Publisher, 2024)
This Study entitled â€œThe Influence Interpersonal Conflict and Group Cooperation To Skills Presentation Office Administrative Education Students Class of 2022.â€ Study This aim for analyze influence Interpersonal conflict and cooperation group to Skills presentation student. The theory used in study This is interpersonal conflict, cooperation, work team, presentation and skills presentation. Study This use method descriptive quantitative with technique determination sample use quota sampling technique. Data obtained based on interviews, observations and filling questionnaire to respondent. Population in research This is students of the Administrative Education study program Medan State University Class of 2022 office with total respondents as many as 56 people. Data analysis techniques used in study This that is using analytical models regression multiple. Research result This show that in a way simultaneous Interpersonal conflict and cooperation group influential significant to Skills presentation students, that is of 30.5%. Whereas in a way Partial Interpersonal conflict is not influential to Skills presentation student.